A Synthesis, Properties and Application as a Possible Drug Delivery Systems Dendrimers – A Review - Salvi, Lavish; Dubey, Chetan Kumar; Sharma, Kapil; Nagar, Devendra; Meghani, Monika; Goyal, Saloni; Nagar, Jagdish Chandra; Sharma, Archana (Asian Journal of Pharmaceutical Research and Development, 2020)
Dendrimer is derived from the Greek word “dendron” which is used for tree and from the Greek suffix “mer” (segment) which describes the synthetic, three-dimensional molecules having branching parts.“A dendrimer is generally described as a macromolecule, which is characterized by its dendritic and hyper branched 3D structure that offers a high degree of surface functionality and versatility.” Dendrimers possess three distinguishable architectural components i.e. an interior core, interior layer(generations) composed of repeating units radially attached to the interior core, and exterior (terminal functionality) attached to outermost interior generation (Fig. 1). The higher generation dendrimers, due to their globular structure, occupy a smaller hydrodynamic volume compared to the corresponding linear polymers. The dendritic structure is characterized by layer between each generation.Dendrimers are generally prepared using either a divergent method or a convergent one. There is a fundamental difference between these two construction concepts. Dendrimers shows the various properties such as structure, shape, aqueous solubility, non-polar solubility, &architecture. Dendrimer can be classification on the basis of their shape, structure, branching, solubility, chirality and attachment. Dendrimer can be differentiated on the basis of their shape, end functional groups and internal cavities.